Web semantics and ontology - Taniar, David; Rahayu, Johanna Wenny (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2006)
This book provides an excellent overview of current research and development activities, while covering an extensive range of topics including ontological modeling, enterprise systems, querying and knowledge discovery, and a wide range of applications. Each chapter contains a thorough study of the topic, systematic proposed work, and a comprehensive list of references
Includes bibliographical references. - Title from ebook home page (viewed on July 24, 2010)
Keywords: Semantic Web; Ontology